Celastrol inhibits pathologic neovascularization in oxygen-induced retinopathy by targeting the miR-17-5p/HIF-1α/VEGF pathway. Issue 19 (2nd October 2022) - Zhao, Kun; Jiang, Yaping; Zhang, Jing; Shi, Jing; Zheng, Pengxiang; Yang, Chuanxi; Chen, Yihui
ABSTRACT: Retinopathy of prematurity (ROP), which is characterized by retinal neovascularization (RNV), is a major cause of neonatal blindness. The primary treatment for ROP is anti-vascular endothelial growth factor (VEGF) therapy, which is costly and can rapidly lead to desensitization. Celastrol, a bioactive compound extracted from Tripterygium wilfordii Hook F. ("Thunder of God Vine"), has been shown to exert anticancer and anti-inflammatory effects. However, whether celastrol has antiangiogenic activity and can suppress inflammation to inhibit ROP progression is unclear. This was investigated in the present study in vitro as well as in vivo using a mouse model of oxygen-induced retinopathy (OIR). Our results showed that celastrol treatment reduced neovascular and avascular areas in the retina and inhibited microglia activation and inflammation in OIR mice. Celastrol also inhibited proliferation, migration, and tube formation in cultured human retinal microvascular endothelial cells, and reversed the activation of the microRNA (miR)-17-5p/hypoxia-inducible factor (HIF)-1α/VEGF pathway in the retina of OIR mice. These results indicate that celastrol alleviates pathologic RNV in the retina by protecting neuroglia and suppressing inflammation via inhibition of miR-17-5p/HIF-1α/VEGF signaling, and thus has therapeutic potential for the prevention and treatment of ROP. Abbreviations: BSA, bovine serum albumin; COX2, cyclooxygenase 2; ECM, endothelial cell medium; FBS, fetal bovine serum; HDAC, histone deacetylase; HIF-1, hypoxia-inducible factor 1; HRMEC, human retinal microvascular endothelial cell; Hsp70, heat shock protein; IB4, isolectin B4; ICAM-1, intercellular adhesion molecule 1; IL-1β/6, interleukin 1 beta/6; MAPK, mitogen-activated protein kinase; MCP-1, monocyte chemoattractant protein 1; miRNA, microRNA; MMP, matrix metalloproteinase; mTOR, mammalian target of rapamycin; NF-κB, nuclear factor-kappa B; OIR, oxygen-induced retinopathy; PBS, phosphate-buffered saline; PCNA, proliferating cell nuclear antigen; PI3K, phosphatidylinositol-3-kinase; qRT-PCR, quantitative real-time PCR; RNV, retinal neovascularization; ROP, retinopathy of prematurity; RTCA, real-time cell analyzer; RVO, retinal vaso-obliteration; TNF-α, tumor necrosis factor alpha; VCAM-1, vascular cell adhesion molecule 1; VEGF, vascular endothelial growth factor.